2010
DOI: 10.1159/000320940
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism in Patients with Gastric Carcinoid Tumors Type 1: An Unusual Coexistence

Abstract: Objective: Although a number of familiar syndromes are associated with primary hyperparathyroidism (PHP), there is no information regarding the prevalence of PHP in other sporadic neuroendocrine diseases. The aim of this study is to investigate the prevalence of PHP in our group of patients with gastric carcinoid (GC) type 1 tumors. Methods: Twenty-six patients with biopsy-proven GC type 1 tumors were retrospectively studied. The diagnosis of PHP was suspected following elevated or high-normal serum calcium le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Primrose et al (12) described the coexistence of hypergastrinemia and achlorhydria, which is suggestive of a diagnosis of CAAG, in 5.2% of 32 patients with PHPT, and Corleto et al (13) demonstrated the presence of CAAG in 7/52 (13.5%) patients with PHPT. On the other hand, Peracchi et al (14) documented the presence of PHPT in 3/52 patients with CAAG (5.8%), whereas Thomas et al (17) did not find PHPT cases in a series of 30 CAAG patients without GC but reported a PHPT prevalence of 15.4% in 26 patients with GC1, suggesting a possible association between GC1 and PHPT rather than between CAAG and PHPT. The coexistence of PHPT and GC1 has been described as a sporadic association in several studies (18,19,20,21,22,23), but the mechanisms (responsible) for this association are still unknown.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Primrose et al (12) described the coexistence of hypergastrinemia and achlorhydria, which is suggestive of a diagnosis of CAAG, in 5.2% of 32 patients with PHPT, and Corleto et al (13) demonstrated the presence of CAAG in 7/52 (13.5%) patients with PHPT. On the other hand, Peracchi et al (14) documented the presence of PHPT in 3/52 patients with CAAG (5.8%), whereas Thomas et al (17) did not find PHPT cases in a series of 30 CAAG patients without GC but reported a PHPT prevalence of 15.4% in 26 patients with GC1, suggesting a possible association between GC1 and PHPT rather than between CAAG and PHPT. The coexistence of PHPT and GC1 has been described as a sporadic association in several studies (18,19,20,21,22,23), but the mechanisms (responsible) for this association are still unknown.…”
Section: Discussionmentioning
confidence: 95%
“…Fujimori et al (26) and Bjorklund et al (27) identified a mutation in exon 3 of the CTNNB1 gene, encoding b-catenin accumulation, both in parathyroid tumours and in carcinoids, but this mutation has not been confirmed in later studies (28,29). An alteration in P21 and P27 has also been suggested (30,31), though their role in ECL and parathyroid oncogenesis remains to be elucidated (17). Overall, further studies are needed to evaluate the possibility of a direct association between GC1 and PHPT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary hyperparathyroidism due to a parathyroid adenoma was the commonest neoplasia. Although the exact etiology of this finding is not known, it is plausible to consider that these tumors may develop as a result of the stimulatory effect of gastrin (30). As most patients had autoimmune gastritis, other autoimmune endocrine disorders, such as Hashimoto's thyroiditis, premature ovarian failure, vitiligo, and diabetes mellitus type 1 were also found to be prevalent (31).…”
Section: Discussionmentioning
confidence: 96%